Research and Comparative Analysis of Flow Field Characteristics and Load-Independent Power Losses of Internal and External Gear Pairs. (10th December 2020) - Zeng, Qing-liang; Sun, Zhi-yuan; Wan, Li-rong; Yang, Yang; Dai, Han-zheng; Yang, Zhi-kuan
Abstract : Power loss analysis of gear transmission in a transmission system is of great significance to improve the efficiency of the power system, and load-independent power losses are an important part of the power losses of gear transmission. Based on the computational fluid dynamics (CFD) method, the hydrodynamic models of internal and external gear pairs are established. By analyzing the pressure field and the velocity field, the windage and squeezing power losses and the pressure and viscous power losses, the influence of rotation speed and tooth width on flow field characteristics, and load-independent power losses of internal gear pair are studied. In addition, we compare the flow field characteristics and the load-independent power losses between external and internal gear pairs and discuss the difference between them. The results show that the pressure and fluid velocity in the meshing area of the gear pair are greatly affected by rotation speed and tooth width, and the load-independent power losses increase with the increase of rotation speed and tooth width. At the same rotation speed, the transmission ratio and number of teeth, windage, and squeezing power losses of the external gear pair are smaller than those of the internal gear pair. Compared with the internal gear pair, the external gear pair has more advantages in controlling the load-independent power losses. The difference of the load-independent power losses of the two meshing modes mainly comes from the viscous power losses of the wheel gear of internal gear pair. This paper provides a basis for the selection of the gear meshing mode and the analysis of load-independent power losses of the transmission system.